Design of a robotic arm for inspecting curved surface in aerospace non-destructive testing - Ajman, Mohd Afiq Azizi; Abdullah, Ermira Junita (The Aeronautical and Astronautical Society of the Republic of China, 2024)
The aerospace industry's reliance on inspections for component safety and readiness prompts challenges in non-destructive testing (NDT), particularly on contoured surfaces. Conventional methods, such as ultrasonic and eddy current testing, require constant probe contact which leads to slow inspections and accuracy concerns. Additionally, technicians face risks during elevated point inspections, necessitating a safer and efficient solution. To address these challenges, this study proposes a specialized robotic arm for NDT inspections in aerospace. The robotic arm automates inspections, enhancing efficiency, accuracy, and technician safety. The research aims to validate the robotic arm's performance, certifying its capability for NDT inspections on curved surfaces which ushers in a new era of enhanced practices. Using CATIA software, the project progresses through preliminary, conceptual, and detailed design stages. The fabricated robotic arm integrates with a trajectory planning and feedback system, enabling curved surface scanning while maintaining a normal probe trajectory. The system yields a 4.3 percent of error emphasizing the system's precision, with rigorous testing using myRIO and infrared (IR) sensor confirming the robotic arm's ability to maintain a 2-mm distance from the scanned surface. This validates the system's efficacy and its capacity to autonomously uphold a specified distance during scanning. This innovative robotic arm and control system significantly impact aviation NDT, improving inspection practices, safety, and industry standards. The study not only validates the robotic arm's effectiveness but also sets the stage for future innovations in robotic NDT, benefiting sectors reliant on quality control and safety. The dual emphasis on precision and safety underscores the transformative potential of this research.